Implementation of Counter-Radicalization Policy Through Online Media at the Security Intelligence Directorate of the Central Sulawesi Regional Police - Iwan; Irfan Mufti, Mohamad; Mustainah (Journal of Public Administration and Government, 2025)
This study aims to analyze the implementation of counter-radicalization policies through online media by the Directorate of Security Intelligence, Central Sulawesi Regional Police. The research is motivated by the increasing spread of radical ideologies through digital platforms utilized by extremist groups such as Mujahidin Indonesia Timur (MIT). Using a qualitative approach and a case study method, the research explores the effectiveness, challenges, and strategies of implementing counter-radicalization policies within Ditintelkam Polda Central Sulawesi. The analysis is based on George C. Edwards III’s policy implementation theory, which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. Supporting frameworks include the Policy Network, Change Management, and Evidence-Based Policy theories. The findings reveal that the implementation of counter-radicalization policies through online media remains suboptimal due to limited inter-agency coordination, insufficient digital human resources, and low community engagement. Nevertheless, ongoing efforts to strengthen cross-sector collaboration and enhance the digital capacity of security officers indicate positive progress toward more effective policy outcomes. This research contributes both academically and practically to the development of digital-based counter-radicalization strategies in Indonesia.